RELATIONSHIP BETWEEN FOREIGN DIRECT INVESTMENT AND STOCK MARKET DEVELOPMENT IN A SMALL SOUTHERN AFRICA ECONOMY - Ngobe, Duduzile; Emenike, Kalu O. (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
This paper investigates the relationship between foreign direct investment and stock market development in a small southern African economy. Specifically, the paper analyses long-run, short-run and causal relationships between foreign direct investment and stock market development in Eswatini for the 1990 to 2018 periods. Results of preliminary analyses of the variable show existence of positive skewness, fat-tailed, non-normal distribution, and I(1) order of integration for the foreign direct investment and stock market return series. Estimates from the ARDL model indicate evidence of a positive and statistically insignificant long-run relationship between foreign direct investment and stock market development in the kingdom of Eswatini. But in the short-run, there exist no relationship between foreign direct investment and stock market development in Eswatini. Estimates from Granger causality test do not show any evidence of causal relationship between foreign direct investment and stock market development in Eswatini. We recommend amongst others that capital market authorities should establish measures to increase the number of listings in the market so as boost investment options. In addition, there should be massive domestic investor-education on benefits of financing projects with a combination capital market funds, which has long-term tenor, and money market funds, which are of short-term nature.